Neuropsychological rehabilitation : theory, models, therapy and outcome. - Wilson, Barbara A., 1941-; Evans, Jonathan J., ....-; Gracey, Fergus, ....- (Cambridge : Cambridge University, 2011)
The aim of neuropsychological rehabilitation is to enable people with cognitive, emotional, or behavioural deficits to achieve their maximum potential in the domains of psychological, social, leisure, vocational or everyday functioning. Describing the holistic programme devised and adopted at the world famous Oliver Zangwill Centre and embracing a broad theoretical base, incorporating a variety of frameworks, theories and models, this book proposes an integrated approach to brain injury rehabilitation by an interdisciplinary team. The coverage explains the underlying principles involved, describes the group therapies employed, highlights a selection of real case examples and reviews the outcomes measured and achieved. This book is essential reading for clinical neuropsychologists, clinical psychologists, speech and language therapists, occupational therapists, psychiatrists, neurologists, physiotherapists, social workers and nurses. * Describes in detail the holistic rehabilitation programme
Devised and adopted at the world famous Oliver Zangwill Centre * Details the therapeutic strategies employed enabling the reader to establish similar group approaches * Includes real case examples illustrating different aspects of holistic rehabilitation Contents Part I. Background and Theory: 1. Towards a comprehensive model of neuropsychological rehabilitation 2. Evidence for the effectiveness of neuropsychological rehabilitation 3. Goal setting as a way of planning and evaluating neuropsychological rehabilitation 4. The Oliver Zangwill Centre approach to neuropsychological rehabilitation Part II. Group Interventions: 5. The Understanding Brain Injury (UBI) 6. The Cognitive Group, part 1: attention and goal management 7. The Cognitive Group, part 2: memory 8. The Mood Management Group 9. The Psychological Support Group 10. Working with families in neuropsychological rehabilitation 11. Communication Group 12. Practically-based project groups Part III. Case Illustrations: 13. Peter: successful
Rehabilitation following a severe head injury with cerebro-vascular complications 14. Lorna: applying models of language, calculation, and learning within holistic rehabilitation - from dysphasia and dyscalculia to independent cooking and travel 15. Caroline: treating PTSD after traumatic brain injury 16. Interdisciplinary vocational rehabilitation addressing pain, fatigue, anxiety and impulsivity: Yusuf and his 'new rules for business and life' 17. Judith: learning to do things 'at the drop of a hat': behavioural experiments to explore and change the 'meaning' in meaningful functional activity 18. Simon: brain injury and the family - the inclusion of children, family members and wider systems in the rehabilitation process 19. Adam: extending the therapeutic milieu into the community in the rehabilitation of a client with severe aphasia and apraxia 20. Malcolm: coping with the effects of Balint's syndrome and topographical disorientation 21. Kate: cognitive recovery and emotional adjustment in
A young woman who was unresponsive for several months Part IV. Outcomes: 22. Is this approach effective? Outcome measurement at the Oliver Zangwill Centre
Keywords: Neurologische aandoeningen; Rehabilitatie